2011
DOI: 10.1007/s11284-011-0879-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of climatic effects on radial growth of evergreen broad‐leaved trees at their northern distribution limit and co‐dominating deciduous broad‐leaved trees and evergreen conifers

Abstract: Using dendrochronological techniques,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
5
8
0
Order By: Relevance
“…Individual trees were treated as a random effect, and the ADGR was calculated for 2002-2007, 2007-2012, 2012-2015) for each tree (Sakai, 1978). Takahashi and Okuhara (2012) showed that growth of evergreen hardwoods is usually restricted by winter cold in the same site as this study. The threshold temperature for tolerance to freezing is between −7°C and −18°C for evergreen hardwoods that distribute up to central Japan (Sakai, 1978).…”
Section: Species Number Of Evergreen Hardwoodssupporting
confidence: 64%
See 3 more Smart Citations
“…Individual trees were treated as a random effect, and the ADGR was calculated for 2002-2007, 2007-2012, 2012-2015) for each tree (Sakai, 1978). Takahashi and Okuhara (2012) showed that growth of evergreen hardwoods is usually restricted by winter cold in the same site as this study. The threshold temperature for tolerance to freezing is between −7°C and −18°C for evergreen hardwoods that distribute up to central Japan (Sakai, 1978).…”
Section: Species Number Of Evergreen Hardwoodssupporting
confidence: 64%
“…Species more tolerant to freezing can distribute in colder areas, and generally tolerance to freezing is greater for deciduous hardwoods than evergreen hardwoods (Sakai, ). Takahashi and Okuhara () showed that growth of evergreen hardwoods is usually restricted by winter cold in the same site as this study. The threshold temperature for tolerance to freezing is between −7°C and −18°C for evergreen hardwoods that distribute up to central Japan (Sakai, ).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Particularly in temperate and cold climates, air temperature is the most important environmental variable along elevational gradients [18]. Previous studies have revealed that a shorter growing season [19] and declining radial growth are general trends as altitude/latitude increases [20,21]. However, whether the shorter duration of xylogenesis is due to later onset, or to earlier cessation remains unclear.…”
Section: Introductionmentioning
confidence: 99%